Kebijakan Birokrasi dalam Upaya Pelayanan Publik Berkualitas - Kisno Hadi (Universitas Islam Indonesia, 2009)
Qualified bureaucracy public services are very much needed in the new global trend. Everylocal government has to respond it and take necessary actions innovatively. This researchexplores about how to create qualified bureaucracy public services, and how is the bestpractices of bureaucracy public services in accordance with regional society. To elaborateon the issues this research maps out bureaucracy reform which has to be done by regionalgovernment, and asserts an example about the process of qualified bureaucracy publicservices in a smallest unit in the government structure. This research reveals that tocreate qualified bureaucracy public services need strong commitment of regional leadersand their stakeholders through among others: reorientation of service mission; changingservice culture; creation of service based education; choosing service culture based politicalleaders; strengthening civil society control.Keywords: bureaucracy, qualified public services, reform, strong commitment.